Quality of nurses' communication with mechanically ventilated patients in a cardiac surgery intensive care unit - Marzieh Momennasab; Mohammadreza Shaker Ardakani; Fereshte Dehghan Rad; Roya Dokoohaki; Reza Dakhesh; Azita Jaberi (Universidad de Antioquia, 2019)
Objective. To describe the quality of the relationship between nurses and patients under mechanical ventilation. Methods. This observational study, performed in a cardiac surgery intensive care unit in Iran, selected 10 nurses and 35 patients through simple random and convenience sampling, respectively. One of the researchers observed 175 communications between nurses and patients in different work shifts and recorded the results according to a checklist. Nurse and patient satisfaction with the communication was assessed by using a six-item Likert scale, 8 to 12 h after extubation. Results. Most of the patients were male (77.1%), while most of the nurses were female (60%). Patients started over 75% of the communications observed. The content of the communication was related mostly to physical needs and pain. Besides, the majority of patients used purposeful stares and hand gestures, and head nod for communication. Most of the communications between patients and nurses were satisfied 'very low' (45.7% in nurses, versus 54.3% in patients). However, 'complete satisfaction' was lower in nurses (0%), compared with patients (5.7%). No statistically significant correlation was found between patients' and nurses' satisfaction and demographic variables. Conclusion. The results showed that communication between nurses and mechanically ventilated patients was built through traditional methods and was based on the patients' requests. This issue might be the cause of an undesirable level of their satisfaction with the communication, given that effective communication can lead to understanding and meeting the needs of the patients. How to cite this article: Momennasab M, Ardakani MS, Rad FD, Dokoohaki R, Dakhesh R, Jaberi A. Quality of Nurses' Communication with Mechanically Ventilated Patients in a Cardiac Surgery Intensive Care Unit. Invest. Educ. Enferm. 2019; 37(2):e02.